Hunting Poses Only a Low Risk for Alveolar Echinococcosis - Wetscher, Monika; Hackländer, Klaus; Faber, Viktoria; Taylor, Ninon; Auer, Herbert; Duscher, Georg G. (Frontiers in Public Health, 2019)
The Austrian province of Tyrol belongs to the areas where the alveolar echinococcosis (AE) caused by the fox tapeworm Echinococcus multilocularis (E. multilocularis) is highly endemic. In Central Europe and since 2011 in Austria, a growing incidence of human cases of AE has been observed, presumably linked with increasing fox populations infected by the fox tapeworm E. multilocularis. Hunting and the related activities put hunters in a high-risk group, and they are considered particularly vulnerable for the contraction of an AE. In light of this risk and the increased number of AE cases made public in Austria, the objective of the study was to investigate the prevalence of AE in hunters and to provide a possible connection to the incidence increase. In 2015 and 2016, we examined 813 serums of active hunters from all nine districts of Tyrol and serologically tested them for E. multilocularis antibodies. Twenty-one (2.58%) positive results in ELISA were detected via Western blot (WB), and only one (0.12%) serum showed a low positive reaction. No lesion in the liver parenchyma could be detected by abdominal ultrasonography in this patient so far, but the risk of developing alveolar echinococcosis remains for this WB-positive hunter. Risk factor analysis of these 813 hunters revealed that 697 (85.7%) hunted red foxes regularly and 332 (40.8%) of those skinned them as well. Three hundred and eighteen (39.1%) out of the 813 hunters were owners of hunting dogs; 89 (10.9%) and 243 (29.9%) were owners of non-hunting dogs and cats, respectively. Our results indicate that hunters do not have a greater risk of infection with E. multilocularis compared to non-hunters in Austria. The cause of the unexpected increase in AE cases in Austria remains unclear.